To show this let us use the first example that we

This preview shows page 25 - 30 out of 48 pages.

To show this let us use the first example that we solved earlier i.e.: 2 3 10 0 x x + - =
Image of page 25

Subscribe to view the full document.

26 Exercise 2.2.2 Solve the following quadratic equations : 2 ( ) 4 5 1 0 a x x + + = ; 2 ( ) 2 2 4 0 b y y - - = ; 2 (c) 12 35 0 y y + + = ; 2 ( ) 9 12 5 0 d a a - - = 2 2 2 3 10 0 3 3 4 1 ( 10) 4 3 9 40 3 49 3 7 2 2 1 2 2 2 3 7 4 2 2 2 3 7 10 5 2 2 + - = - ± - × × - - ± - - ± + - ± - ± = = = = = × - + = = = - - - = = = - x x a b c b b ac x a x or x We have 2 solutions: 2 5 x or x = = - . If you check the solution we got earlier using the other method you will see that the results are exactly the same. Extra Exercises for Practice Solve these equations 2 2 2 2 2 ( ) 4 10 6 0; ( ) 3 6 0; ( ) 12 16 16 0; ( ) 3 6 0; ( ) 6 15 18 - + = - = + - = - = + = a x x b y y c p p d x x e a a
Image of page 26